AUTONOMIA PROCEDURALNA PAŃSTW CZŁONKOWSKICH. ZASADA EFEKTYWNOŚCI I ZASADA EFEKTYWNEJ OCHRONY SĄDOWEJ W PRAWIE UNII EUROPEJSKIEJ - Wróbel, Andrzej (Wydział Prawa i Administracji UAM, 2005)
This paper focuses on the relationship between the so called ‘procedural autonomy’ of the Member States on the one hand and the principles of effectiveness and effective judicial protection in the European Community law on the other. In Rewe and Comet judgments the ECJ holds that the creation of individual rights is a matter of Community law, while the remedies for the enforcement of these rights are - in the absence of relevant Community legal provisions - to be provided by national (procedural) law. In this context, it is obvious that the effectiveness of Community rights depends on national procedural rules. However, this national procedural autonomy is restricted by two important requirements: firstly, such rules are not less favourable than those governing similar domestic actions (the principle of equivalence) and secondly, they do not render the exercise of Community rights virtually impossible or excessively difficult (the principle of effectiveness). Recent European legislative interventions in procedural matters show that the concept of national procedural and institutional autonomy of the Member States no longer explains the very complicated relationship between the European substantive law and national procedural rules. This is rather a question of division of competences in procedural matters between the Member States and Communities and procedural harmonization than the somewhat obscure concept of autonomy. On the other hand, the principle o f effectiveness starts to play a crucial role in the protection of individual Community rights in national courts, so that it replaces the principle of primacy of Community law in those matters. However, the ECJ has developed the principle of effective judicial protection, which has received the rank of a fundamental Community legal principle. This principle can be regarded as more appropriate than the former one, to protect Community rights at the national level and within national procedural competences.
PROCEDURAL AUTONOMY OF EU MEMBER STATES: PRINCIPLE OF EFFECTIVENESS AND EFFECTIVE JUDICIAL PROTECTION